Fisetin inhibits growth, induces G2/M arrest and apoptosis of human epidermoid carcinoma A431 cells: role of mitochondrial membrane potential disruption and consequent caspases activation. Issue 7 (25th June 2013) - Pal, Harish C.; Sharma, Samriti; Elmets, Craig A.; Athar, Mohammad; Afaq, Farrukh
Abstract Non‐melanoma skin cancers (NMSCs), one of the most common neoplasms, cause serious morbidity and mortality. Therefore, identification of non‐toxic phytochemicals for prevention/treatment of NMSCs is highly desirable. Fisetin (3, 3′, 4′, 7‐tetrahydroxyflavone), a dietary flavonoid, present in fruits and vegetables possesses anti‐oxidant and antiproliferative properties. The aim of this study was to investigate the chemotherapeutic potential of fisetin in cultured human epidermoid carcinoma A431 cells. Treatment of A431 cells with fisetin (5–80 μm) resulted in a significant decrease in cell viability in a dose‐ and time‐dependent manner. Employing clonogenic assay, we found that fisetin treatment significantly reduced colony formation in A431 cells. Fisetin treatment of A431 cells resulted in G2/M arrest and induction of apoptosis. Furthermore, treatment of A431 cells with fisetin resulted in (i) decreased expression of anti‐apoptotic proteins (Bcl2; Bcl‐xL and Mcl‐1); (ii) increased expression of pro‐apoptotic proteins (Bax, Bak and Bad); (iii) disruption of mitochondrial potential; (iv) release of cytochrome c and Smac/DIABLO from mitochondria; (v) activation of caspases; and (vi) cleavage of Poly(ADP‐ribose) polymerase (PARP) protein. Pretreatment of A431 cells with the pan‐caspase inhibitor (Z‐VAD‐FMK) blocked fisetin‐induced cleavage of caspases and PARP. Taken together, these data provide evidence that fisetin possesses chemotherapeutic potential against human epidermoid carcinoma A431 cells. Overall, these results suggest that fisetin could be developed as a novel therapeutic agent for the management of NMSCs.